Why making good on green promises can be a win for retailers : retailers that take the lead on engaging employees on environmental sustainability can strengthen culture, talent retention, and employee satisfaction - Sides, Rodney R.; Skelly, Lupine (MIT Sloan Management Review, 2022)
A Deloitte research team surveyed 750 U.S. retail employees on their perceptions of their employers’ sustainability progress. The findings revealed that retailers demonstrating authentic sustainability efforts might have better success attracting and retaining labor. Employees at retailers with strong sustainability cultures are much more likely to be highly engaged and satisfied and are less likely to seek new jobs.